Performance Evaluation of Select Mutual Funds: A Public-Private Comparison - Rehmani, Amir (Indian Journal of Finance, 2018)
The present study attempted to evaluate the investment performance of select public and private sector mutual fund schemes against risk-free rate and benchmark/market index for a period of 7 financial years, that is, from 2010 to 2017 (84 months). The sample included a total of 8 equity/growth schemes, 4 from public sector and 4 from private sector. For the analysis, monthly NAV of sample schemes were taken, and monthly closing values of BSE 100 were considered as the benchmark index, 91-days treasury bills were taken as the risk-free rate. Risk return analysis along with analysis of risk-adjusted performance measures such as Sharpe ratio, Treynor ratio, Jensen measure, and Sharpe-differential measure were used for evaluating the investment performance of the selected sample schemes. The findings of the study revealed that private sector funds outperformed the public sector funds against their benchmark index in terms of risk-return analysis as well as risk-adjusted measures of performance evaluation throughout the study period, and it was also observed that among the schemes, small and mid cap category of schemes of both the sectors were the top performers.